KONFLIK PERAN GANDA DAN STRES KERJA POLISI WANITA DI POLDA SULAWESI SELATAN - Rosmila Sari; St. Nurhikma Maulida (Jurnal Administrasi Negara, 2021)
Policewomen who carry out two roles, namely as a woman's nature and also her duties as a police officer are certainly not easy. Being a good housewife and being a good policewoman is a role that must be carried out. Two roles carried out by a woman often experience dual role conflicts which result in work stress and will affect the performance of the policewoman. Based on these problems, this study aims to determine the description of work stress in terms of the dual role conflict of Polwan Polda South Sulawesi. The research method used in this research is descriptive qualitative method. Data collection techniques were carried out by interview, observation and documentation methods. The results showed that the dual role conflict affected the work stress of the Polwan Polda South Sulawesi. Work stress causes performance to decline by continuing to buy time in completing work, conflicts within oneself and makes a person more emotional, becomes lazy to attend morning apples and does not focus on work, affects job satisfaction, work stress causes work to be neglected and reduced work productivity.